Effects of Integrated Polyethylene and Cover Crop Mulch, Conservation Tillage, and Herbicide Application on Weed Control, Yield, and Economic Returns in Watermelon. (October 2018) - Price, Andrew J.; Williams, Jacob P.; Duzy, Leah A.; McElroy, J. Scott; Guertal, Elizabeth A.; Li, Steve
Abstract: A 3-yr watermelon experiment was established in fall 2013 to evaluate cover crop, polyethylene mulch, tillage, and herbicide application components for weed control, yield, and profitability. Conservation tillage, either with a cereal rye cover crop alone or integrated with polyethylene mulch, was compared to the standard industry practice of conventional tillage with bedded polyethylene mulch. The study also used a non-bedded conventional tillage system without polyethylene to determine polyethylene and cover crop residue effects. Within each of the four systems, herbicide treatments comprised halosulfuron applied (1) at 26.3 g ai ha –1 PRE, (2) at 26.3 g ai ha –1 POST, or (3) sequentially at 26.3 g ai ha –1 PRE and POST. Each system also had a nontreated control. In addition, clethodim was applied in all plots twice POST at 140 g ai ha –1, except for nontreated in each system. In 2014, polyethylene or cereal rye cover crop effectively controlled tall morningglory, coffee senna, and carpetweed early season in nontreated plots, whereas the integration of the two was effective at controlling common purslane. Tall morningglory and purslane control was insufficient late season regardless of production system and herbicide application. In 2015, polyethylene effectively controlled cutleaf eveningprimrose, sicklepod, and arrowleaf sida early season in nontreated plots. Yellow nutsedge control was insufficient late season regardless of production system and herbicide application. Utilizing sequential halosulfuron applications did not increase weed control over PRE or POST alone in all years. Polyethylene use resulted in yields higher than systems without in all years. Across all 3 yr, net returns were highest for polyethylene mulch systems. The results of this experiment underscore the need for more progress in developing integrated conservation systems for watermelon production. Effective herbicides, low-disturbance cultivation, and/or hand weeding are most likely the key to success in conservation specialty crop systems.